1996
DOI: 10.1097/00005344-199608000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adenine Nucleotide Analogues on Myocardial Dysfunction During Reperfusion After Ischemia in Dogs

Abstract: We examined effects of adenine nucleotide on ischemic myocardial stunning in dogs. Pentobarbitalanesthetized open-chest dogs were subjected to 20-min ligation of the left anterior descending coronary artery (LAD), followed by reperfusion for 30 min. Either saline, 5 mM 8-bromo-5'-AMP (tributyryl-AMP), or 30 mM N6, 2', 3'-tributyryl-5'-AMP (tributyryl-AMP), 5 mM 5-amino-4-imidazole carboxamide riboside (AICAr) as a positive reference, was infused at 0.1 ml/kg/min in the left femoral vein throughout the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Inhibition of NF‐κB activation is already thought to have a major role in the anti‐inflammatory actions of glucocorticoids and salicylates. Inhibition of NF‐κB would also offer an additional reason for the success of AICAR in preventing or reducing ischaemic tissue damage 29 , 30 as it is well known that NF‐κB is activated by hypoxia 31…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of NF‐κB activation is already thought to have a major role in the anti‐inflammatory actions of glucocorticoids and salicylates. Inhibition of NF‐κB would also offer an additional reason for the success of AICAR in preventing or reducing ischaemic tissue damage 29 , 30 as it is well known that NF‐κB is activated by hypoxia 31…”
Section: Discussionmentioning
confidence: 99%
“…Preconditioning ϩ 8-bromo-AMP (PCϩIϩbAMP) (n ϭ 6): Same as group 7, but with previous administration of 5 mmol/L 8-bromo-AMP, 0.1 mL/kg/min intravenously during 30 minutes before preconditioning. 26,27 10. Preconditioning ϩ araA (PCϩIϩaraA) (n ϭ 6): Same as group 7, but with previous administration of araA at 100 g/kg/min during 10 minutes before preconditioning.…”
Section: Experimental Designmentioning
confidence: 99%
“…We [10] have demonstrated that enalapril and telmisartan improve contractile dysfunction of the stunned myocardium, and that the former action is due to inhibition of bradykinin breakdown, whereas the latter is due to a direct block of myocardial AT 1 receptors. Ischemia depletes the ATP store in the myocardium, and reperfusion can restore it with ATP, but incompletely [15,16] . Both telmisartan and olmesartan enhance the restitution of ATP after ischemia.…”
Section: Discussionmentioning
confidence: 99%